EVALUATION OF BIOETHANOL PRODUCTION FROM Eucalyptus WOOD WITH Saccharomyces cerevisiae AND SACSV-10 1 - Vazquez,Sylvia Enid (2017)
ABSTRACT Eucalyptus spp. residues of paper industry are a potential lignocellulosic raw material for production of second-generation bioethanol as an alternative to conventional production from cereal crops. Studying the behavior at 40 ºC of a commercial cellulase (Sunson), Eucalyptus sawdust saccharification was carried out under two pH conditions. With the aim to evaluate the bioethanol production from Eucalyptus wood, a strategy combining saccharification and Simultaneous Saccharification and Fermentation (SSF) was undertaken at 40 ºC with a thermotolerant Saccharomyces cerevisiae with different substrate and inoculum concentrations, and different nitrogen sources. At last, the process was carried out in optimal conditions with Saccharomyces cerevisiae M522 and SacSV-10. Saccharification produced more free glucose at pH 5, reaching a maximum of 1.5 g/L. Encouraging results were obtained with 500 mg/L of ammonium sulphate as a nitrogen source and 10 % v/v initial inoculum at 106 cfu/mL concentration. Yeast SacSV-10 was not inhibited by phenols present in the culture media using a wood concentration of 10 g/L, but when the solids concentration was increased, the bioprocess yield was compromised. When the process was carried out in optimal conditions the bioethanol production, expressed as the conversion percentage of cellulose to ethanol, was 71.5 % and 73.6 % for M522 and the mutant strain respectively. The studied properties of the mutant strain provide added value to it, which pose new challenges to national companies dedicated to the production and sale of inputs for bioethanol industry.